2024
DOI: 10.1037/mgr0000151
|View full text |Cite
|
Sign up to set email alerts
|

What executive leadership competencies matter most to patient experience: A national qualitative inquiry.

Laurie A. Latvis,
John W. Fick,
Lihua Dishman

Abstract: Patient experience is the sum of all interactions that influence a patient's perception across the continuum of care. Hospital executive leaders' leadership competencies impact their organizations' patient experience performance. This national, cross-sectional, qualitative study aimed to identify what health care leadership competencies mattered most to patient experiences in U.S. inpatient acute care hospitals. The target population encompassed all inpatient acute care hospitals. A purposive sampling method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Human Resources is the process of empowering humans as workers in a humane manner so that all their physical and psychological potential functions optimally to achieve goals [13].…”
Section: Human Resourcesmentioning
confidence: 99%
“…Human Resources is the process of empowering humans as workers in a humane manner so that all their physical and psychological potential functions optimally to achieve goals [13].…”
Section: Human Resourcesmentioning
confidence: 99%
“…This special issue contains seven articles spanning a wide variety of research questions and methods on the topic of leadership in health care. Latvis et al (2024) sought to determine what health care leadership competencies mattered most to patient experiences in U.S. inpatient acute care hospitals. Through a national study of executive leaders from 28 hospitals, they concluded that the top competencies that mattered most to improving patient experience include change leadership, self-awareness, self-confidence, human resource management, collaboration, team leadership, initiative, accountability, professional and social well-being, verbal communication, process and quality improvement, community collaboration, analytical thinking, achievement orientation, and organizational awareness.…”
mentioning
confidence: 99%